Vaccine hesitancy among nurses in the Marche Region - Fortunato, Corinna; Gasperini, Beatrice; Mengarelli Rinaldini, Davide; Peconi, Chiara; Lanari, Alice; Sarti, Donatella; Pelusi, Gilda (Annali di Igiene Medicina Preventiva e di Comunità, 2025)
Background. Vaccine hesitancy is considered one of the top ten threats to global health by the World Health Organization due to the potential public health consequences. Since April 1, 2021, the Italian Government has made COVID-19 vaccination mandatory for healthcare workers. Those who refused to undergo vaccination were suspended from activities involving patient care. This study aims to describe vaccine hesitancy among nurses in the Marche Region one year after the start of the COVID-19 vaccination campaign. Study design. Observational study. Methods. All nurses belongijg to the National Federation of Nursing Professions Orders of the Marche Region were included in the study. Data from December 27, 2021, to January 1, 2022, were provided by the FNOPI Presidents of provincial FNOPI for Pesaro-Urbino, Ancona, Macerata and Fermo. Results. Among the 9,611 registered nurses, 1.34% were suspended because they refused to be vaccinated. The majority of suspended nurses were women (73.6%), 35.7% aged 50-59 years, and 29.4% aged 40-49 years, 21.7% aged 30-39 years, 10.1% aged ≥60 years and 3.8% aged